EXPANDING DEMAND FOR ONLINE HIGHER EDUCATION: SURVEYING PROSPECTIVE STUDENTS - Garrett, Richard (Online Learning, 2007)
The Eduventures survey examined next-generation demand for online postsecondary education, assessing online experience, delivery mode and marketing channels preferences, and perceptions of price, quality and location, identifying key takeaways in each area